Neuroscience Integration in Secondary Education : A Bibliometric Analysis (1993-2025) - Zayyana Ulfah, Siti; Yulia, Cica; Sudiapermana, Elih; Depriya Kembara, Maulia; Sujana, Atep (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aimed to explore the intersection of neuroscience and education by analyzing how neuroscientific research informs secondary education, particularly in relation to cognitive development, motivation, and learning strategies. Method: A bibliometric analysis of 218 articles indexed in the Scopus database from 1993 to 2025 was conducted. Keyword co-occurrence mapping, citation tracking, and publication trend analysis were performed using VOSviewer to identify core themes and leading contributors in the field. Results: Findings revealed a growing scholarly interest in applying neuroscience to education, especially in areas such as emotional and cognitive regulation, memory, and attention. Foundational studies from 2006 to 2012 remain influential, though the literature still lacks practical integration of neuroscientific findings into secondary-level teaching practices. Novelty: This study offers a structured overview of the educational neuroscience landscape with a unique focus on secondary education, highlighting the need for stronger interdisciplinary collaboration to bridge theory and practice and proposing that neuroscience-informed strategies can improve learning outcomes when aligned with classroom realities.